2016
DOI: 10.4103/0253-7613.193311
|View full text |Cite
|
Sign up to set email alerts
|

Role-play as an educational tool in medication communication skills: Students’ perspectives

Abstract: Objectives:Medication communication skills are vital aspects of patient care that may influence treatment outcomes. However, traditional pharmacology curriculum deals with imparting factual information, with little emphasis on patient communication. The current study aims to explore students’ perceptions of role-play as an educational tool in acquiring communication skills and to ascertain the need of role-play for their future clinical practice.Materials and Methods:This questionnaire-based study was done in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 13 publications
1
20
0
4
Order By: Relevance
“…among medical students during their preclinical years, which means that health-care centers are not providing enough of these resources. Use of simulated patients, role-plays and other learning techniques should be enhanced among medical students prior to their experience with real patients, as they have shown to improve students' communicating skills, con dence and teamwork [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…among medical students during their preclinical years, which means that health-care centers are not providing enough of these resources. Use of simulated patients, role-plays and other learning techniques should be enhanced among medical students prior to their experience with real patients, as they have shown to improve students' communicating skills, con dence and teamwork [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…O role-play é uma técnica de ensino na qual os participantes assumem determinado papel e interagem com outras pessoas em um cenário específico, tentando agir como o personagem agiria na situação que imita a vida real e que pode ser aplicada em diversos aspectos da comunicação médico-paciente. 11,12 Essa técnica pode ser utilizada com pacientes simulados, atores, estudantes veteranos ou mesmo colegas de classe e está baseada numa série de etapas: (a) preparação da atividade pelo facilitador; (b) criação de um ambiente seguro e favorável à aprendizagem; (c) escolha e uso do cenário a ser simulado; (d) condução da sessão; (e) feedback 13 .…”
Section: Discussionunclassified
“…It also gives a space for learners to practise and receive feedback [27]. Previous studies have shown that role play is effective in enhancing communication skills [28,29], in addition recent studies have shown that students consider peer-role play as an essential tool to acquire effective communication skills [30].…”
Section: Discussionmentioning
confidence: 99%